FEMALE FLIRTING IN MISS PETTIGREW MOVIE - Wiruma Titian Jayadi; Evi Sumarlin (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2017)
The aims of this research are to identify flirting used in the movie and the message behind the flirting and their effects. Relying upon qualitative method,  data were analyzed using constant comparison methods. Steps of collections included: watching the movie, reading  books which contain of flirting of speaking, putting the theory of flirting into a movie to select the movie that can be explored by the theory, and identifying the type of flirting speaking based on the movie. The female flirting constituted real data about the elements of women language, and interpretations meaning from the effect of female flirting in speaking. The results of this research indicated that female flirting has some styles of language that can be seen from the element of women language. Evidently, types of meaning which can help to know the interpretations and the effects of female flirting appeared in the movie.